Task-based approaches to teaching and assessing pragmatics - Taguchi, Naoko, 1967-; Kim, Youjin (Task-based language teaching,, 2018)
"This volume is the first book-length attempt to bring together the fields of task-based language teaching (TBLT) and second language pragmatics by exploring how the teaching and assessment of pragmatics can be integrated into TBLT. The TBLT-pragmatics connection is illustrated in a variety of constructs (e.g., speech acts, honorifics, genres, interactional features), methods (e.g., quantitative, quasi-experimental, conversation analysis), and topics (e.g., instructed SLA, heritage language learning, technology-enhanced teaching, assessment, and discursive pragmatics). Chapters in this volume collectively demonstrate how the two fields can together advance the current practice of teaching language for socially-situated, real-world communicative needs"--